2022
DOI: 10.1017/s0007114522003944
|View full text |Cite
|
Sign up to set email alerts
|

Milk–cereal mix supplementation during infancy and impact on neurodevelopmental outcomes at 12 and 24 months of age: a randomised controlled trial in India

Abstract: Inadequate protein intake and lack of micronutrients may affect neurodevelopment in infants. This randomized controlled trial was conducted to measure the effect of two milk-cereal mixes with modest and high amounts of protein and enriched with multiple micronutrients (MMN), given between 6-12 months, on cognitive, language, motor and behavioural scores at 12 and 24 months of age, compared to no-supplementation. The two supplements were also compared with each other. The study was conducted in urban Delhi, Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, some randomized controlled trials have shown that some neurodevelopmental improvements with interventions of high nutritional value. In a randomized controlled trial of supplemental protein intake and micronutrient intake in India that included over 2,000 infants, motor scores were improved by a mean of 1.52 points (95% CI: 0·28, 2·75) at 12 months, there were no differences in developmental scores at 24 month ( 37 ). However, a trial of zinc, iron, and copper supplementation starting at 6 months in 251 infants in Peru with Bayley assessments at 18 months reported no significant neurodevelopmental benefits ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some randomized controlled trials have shown that some neurodevelopmental improvements with interventions of high nutritional value. In a randomized controlled trial of supplemental protein intake and micronutrient intake in India that included over 2,000 infants, motor scores were improved by a mean of 1.52 points (95% CI: 0·28, 2·75) at 12 months, there were no differences in developmental scores at 24 month ( 37 ). However, a trial of zinc, iron, and copper supplementation starting at 6 months in 251 infants in Peru with Bayley assessments at 18 months reported no significant neurodevelopmental benefits ( 38 ).…”
Section: Discussionmentioning
confidence: 99%